2022
DOI: 10.3390/hydrology9120217
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Hydraulic Efficiency of a Steerable Detention Tank—Simulation Studies

Abstract: The article contains the results of the first part of the research on the analysis of the operation of the retention device cooperating with the drainage system—steerable detention tank and concerns model simulation studies. The obtained results are an introduction to conducting laboratory tests. The planned research was carried out on the basis of the theory of experimental planning and hydrodynamic modelling, in which the systems of hydraulic parameters of the drainage system and hydrological of the catchmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…LID refers to techniques and principles that aim to reduce stormwater runoff into sewers, recharge groundwater, increase infiltration, and protect rivers and watercourses. Achieving these goals enables the use of solutions such as retention reservoirs [12,13], infiltration facilities and devices [14,15], and rainwater-harvesting systems [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…LID refers to techniques and principles that aim to reduce stormwater runoff into sewers, recharge groundwater, increase infiltration, and protect rivers and watercourses. Achieving these goals enables the use of solutions such as retention reservoirs [12,13], infiltration facilities and devices [14,15], and rainwater-harvesting systems [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Garbanzos and Maniquiz-Redillas, [7] assessed the hydrologic performance and costeffectiveness of LID in a residential park area in the Philippines and recommended that determining the target capture goal, applicable LID types, and cost estimations from a pilot project are vital components in the future application of LIDs in these regions. Pochwat and Pizzo [8] revealed that the use of a detention tank may significantly reduce the amount of sewage outfall from a drainage system, and that the method of connecting the device to a network has an influence on its efficiency. Humphrey et al [9] evaluated the nitrogen treatment efficiency of a detention basin (DB) that exhibited some wetland characteristics.…”
mentioning
confidence: 99%